Landscape And Landscape City Areas - Mutalova Barno Irgashevna; Abdullayeva Kamilla Djavdatovna (Peerian Journals Publishing, 2022)
This article discusses the main aspects of the improvement of the city
Keywords: architecture; aesthetics; cultural genesis; ethnogenesis